Exploring the effect of a sweltering environment on the risk of death from cardiovascular diseases - Chen, Zhaocong; Li, Wangchao; Zhu, Zhengjie; Miao, Xueliang; Jiang, Shuai; Li, Caiming (Frontiers in Neurology, 2024)
BackgroundA substantial body of research has demonstrated a notable impact of hot temperatures on mortality from cardiovascular diseases (CVDs). However, a paucity of studies has addressed the influence of sweltering conditions on CVD mortality.ObjectiveTo investigate the effect of sweltering conditions on mortality from CVD among permanent residents of Huizhou City, using the temperature-humidity index (THI) as an indicator.MethodsThis study employs descriptive statistics, distributed lag non-linear model (DLNM) and general algebraic modeling system (GAMs) with the THI as an indicator in order to examine the impact of sweltering conditions on the mortality of CVD among permanent residents of Huizhou City.ResultsSweltering conditions increase the risk of death from CVDs and have a cumulative lag effect. The greater the THI, the more pronounced the increase in mortality, and after a certain range, the mortality rate from CVDs increases significantly, and the effect is gender-specific. The lag effect generally peaks in 2–3 days, and the lag effect of stroke mortality is longer and deeper than that of coronary heart disease (CAD) mortality.ConclusionSweltering increased the mortality of cardiovascular diseases in Huizhou city, so we should pay attention to public health intervention strategies under sweltering.